The combined methionine and cystine requirement of growing cockerels in the tropics - NWOKORO, SMART O (The Indian Journal of Animal Sciences, 2014)
Methionine + cystine (met + cys) requirements of cockerels aged between 8 and 16 weeks of age was studied by the nutrient-response relationship. Experimental diets were prepared by supplementing common basal diets with graded levels of met such that dietary met ranged between 0.21 and 69% of the diet. The birds were fed and watered ad lib. for 56 days (8-16 weeks). Dietary supplementation increased weight gain, feed conversion efficiency and protein efficiency ratio (PER) with optimal levels obtained between 0.29% (met .55% met + cys) and 0.37% met (0.63% met + cys). The dressing percentage was significantly affected by dietary treatments but optimal level (0.29%) was lower than where highest weight gain and feed efficiency were obtained.